2011
DOI: 10.1002/ppul.21410
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chorioamnionitis on exhaled nitric oxide and endotracheal aspirate levels of nitrites–nitrates and interleukin‐8 in mechanically ventilated preterm neonates

Abstract: ObjectivesTo assess the influence of maternal chorioamnionitis on early exhaled nitric oxide (NO) and levels of nitrites–nitrates and interleukin (IL)‐8 in endotracheal aspirate fluid in mechanically ventilated preterm neonates.Study DesignCross‐sectional study.Patient–Subject SelectionBetween September 2007 and August 2009, 54 mechanically ventilated preterm neonates were included. Patients were divided into two groups according to the presence or absence of maternal chorioamnionitis, and those without chorio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Sedated, intubated, or awake with spontaneous breathing: Infants and newborns, especially premature infants, have an irregular breathing pattern easily affected by external impacts. Therefore, many lung function and FeNO studies have been performed on sedated and intubated infants [17]. However, intubation seems to affect the levels of FeNO, and the clinical relevance of testing lung function in a sedated state is doubtful [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedated, intubated, or awake with spontaneous breathing: Infants and newborns, especially premature infants, have an irregular breathing pattern easily affected by external impacts. Therefore, many lung function and FeNO studies have been performed on sedated and intubated infants [17]. However, intubation seems to affect the levels of FeNO, and the clinical relevance of testing lung function in a sedated state is doubtful [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many lung function and FeNO studies have been performed on sedated and intubated infants [17]. However, intubation seems to affect the levels of FeNO, and the clinical relevance of testing lung function in a sedated state is doubtful [17].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies report that premature infants affected by any type of chorioamnionitis require resuscitation more often and more extensively at birth (Table 1) [9,[16][17][18][19][20][21][22][23][24][25][26][27]. The increased requirement of resuscitation consisted of associations between chorioamnionitis and any resuscitation/ventilatory support in four studies [17,20,21,23]; oxygen supplementation in two studies [9,23]; and intubation, cardiopulmonary resuscitation or volume expansion in six studies [16,18,19,21,24,26,27]. Pietrasanta et al observed that only a foetal inflammatory response (i.e.…”
Section: Chorioamnionitis and Breathing Effort At Birthmentioning
confidence: 99%
“…13,15,16 Longitudinal eNO measurements from birth may offer valuable prognostic information. [17][18][19][20] As lungs mature and develop rapidly after birth, it is reasonable to believe that measuring eNO may enlighten some of the processes involved. 7,21 Furthermore, it might help diagnosing neonatal respiratory disorders.…”
Section: Introductionmentioning
confidence: 99%